Adam as Israel : Genesis 1-3 as the introduction to the Torah and Tanakh - Postell, Seth D. (Eugene, Or. : Pickwick Publications, 2011)
In this text-centered interpretation of Genesis 1-3, Seth Postell contends that the opening chapters of the Bible, when interpreted as a strategic literary introduction to the Torah and the Tanakh, intentionally foreshadow Israel's failure to keep the Sinai Covenant and their exile from the Promised Land, in order to point the reader to a future work of God, whereby a king will come in "the last days" to fulfill Adam's original mandate to conquer the land (Gen 1:28). Thus Genesis 1-3, the Torah, and the Hebrew Bible as a whole have an eschatological trajectory. Postell highlights numerous intentional links between the y of Adam and the story of Israel and, in the process, explains numerous otherwise perplexing features of the Eden story.
Includes bibliographical references (p. 169-180) and index.
Keywords: Adam -- (Biblical figure); Bible. -- Criticism, interpretation, etc; Intertextuality in the Bible; Jews -- History